Capacidad de respuesta a emergencias epidémicas: recomendaciones para la autoevaluación nacional Response capacity for epidemic emergencies: recommendations for country self-evaluation - Angela Gala (Pan American Health Organization, 2005)
Communicable diseases that have appeared or reappeared in recent years have demonstrated their great potential for spreading and their capacity to overwhelm a country's resources, causing major emergencies. The recent SARS epidemic showed that only health systems that have been strengthened and that have the response capacity for events of this kind will be able to handle future contingencies. Governments have recognized the need to support initiatives to strengthen their countries' capacities in surveillance, prevention, and the control of emergencies caused by epidemics. This piece identifies essential components that will make it possible to guide the efforts of governments, with the support of the Pan American Health Organization and other international organizations, toward achieving a common goal: establishing for countries warning and epidemic-emergency response systems that are appropriate and effective.